Potential adverse cardiac remodelling in highly trained athletes: still unknown clinical significance. Issue 9 (21st October 2018) - Gabrielli, Luigi; Sitges, Marta; Chiong, Mario; Jalil, Jorge; Ocaranza, María; Llevaneras, Silvana; Herrera, Sebastian; Fernandez, Rodrigo; Saavedra, Rodrigo; Yañez, Fernando; Vergara, Luis; Diaz, Alexis; et al.
Abstract: Moderate endurance exercise has long been considered an essential element to maintain cardiovascular health, and sedentary behaviour in the general population has been related to a significant increase in all-causes of mortality, cardiovascular disease mortality and cardiovascular disease incidence. However, a growing group of people performs an intense exercise that leads to multiple heart adaptive changes that are collectively called "athlete's heart". In this review, we discussed the evidence of cardiac remodelling process secondary to repetitive and strenuous exercise in some predisposed athletes that produces intense and probably deleterious changes in cardiac morphology and function with no clear clinical significance in long-term follow-up. Moreover, we also discussed the individual biological response to exercise assessed by myocardial damage, inflammation, oxidative stress, fibrosis and ventricular hypertrophy biomarkers showing different intensities with equivalent exertion.